2017
DOI: 10.2147/copd.s136404
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic ECG abnormalities are associated with an increased risk for death among subjects with COPD, also among those without known heart disease

Abstract: presentation An abstract, including parts of the results, has been presented at an oral session at the European Respiratory Society International Conference, London, UK, September 2016. Background Cardiovascular comorbidity contributes to increased mortality among subjects with COPD. However, the prognostic value of ECG abnormalities in COPD has rarely been studied in population-based surveys. Aim To assess the impact of ischemic ECG abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 41 publications
1
13
0
10
Order By: Relevance
“…The risk of death also persisted after adjustment for COPD severity. 70 Underuse of beta-blockers, statins, and antiplatelet drugs is frequent in patients with IHD and COPD, and possibly contributes to a worse prognosis. 71,72 Nevertheless, even in patients with IHD adequately treated, the presence of COPD confirmed by spirometry is associated with an increase in cardiovascular events and mortality during the follow-up.…”
Section: Primary Studiesmentioning
confidence: 99%
“…The risk of death also persisted after adjustment for COPD severity. 70 Underuse of beta-blockers, statins, and antiplatelet drugs is frequent in patients with IHD and COPD, and possibly contributes to a worse prognosis. 71,72 Nevertheless, even in patients with IHD adequately treated, the presence of COPD confirmed by spirometry is associated with an increase in cardiovascular events and mortality during the follow-up.…”
Section: Primary Studiesmentioning
confidence: 99%
“…The study design of the Obstructive Lung Disease in Northern Sweden (OLIN) COPD study has previously been described in detail [7,17]. In summary, the COPD population in this study (n = 993) was identified after reexamination including spirometry of four previously recruited population-based cohorts in 2002-04 (n = 4200), together with n = 993 non-obstructive referents matched by age and sex.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…Still, patients with COPD may be less likely to receive cardiovascular preventative therapies [5], albeit most guidelines for diagnosis and treatment of COPD [6] include recommendations regarding evaluation of cardiovascular risk factors and the presence of cardiovascular disease. However, no biomarker has been shown to identify subclinical cardiovascular disease in a representative population-based cohort of individuals with COPD, even though ischemic abnormalities on electrocardiogram (ECG) are suggested to be associated with worse prognosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Severity of COPD: by making the mild stage of COPD reference, other stages are 3.2 more likely to develop abnormal ECG/AOR 3. 27,31 This is mainly due to the exacerbation of the disease resulting in systemic comorbidities including CVDs as evidenced by ECG.…”
Section: Discussionmentioning
confidence: 99%
“…The identified factors for ECG changes were amount of systemic C-reactive proteins (CRP) as markers of inflammation, hypoxia, duration and severity of COPD which was exacerbated by mutual risk factors smoking and aging. [26][27][28][29][30][31][32][33] Thus, the current study aimed to explore and detect changes of ECG pattern by using the 12 lead ECG which is not routinely performed especially in developing countries including Ethiopia and the study area due to economic constraints and determine the associated risk factors among COPD patients.…”
Section: Introductionmentioning
confidence: 99%